Fundamentals of cell metabolism and cancer - Devendran, Ragunathan; Ramesh, Vignesh; Gnanasekaran, Prabu (Elsevier, 2022)
Cancer, a highly heterogeneous disease, arises from the spontaneous selection of advantageous molecular level processes favoring cell proliferation and growth. Uncontrolled cell proliferation and growth cause irregular nutrient turnover during tumor development. Cancer cells prime the metabolic rewiring to achieve a proliferative capacity for survival under such conditions. In other words, altered metabolism is the fundamental difference between normal and cancer cells. Interestingly, metabolic pathways serve as suitable and promising targets for therapeutics. Therefore, understanding the metabolism of the normal and cancerous state is essential to develop therapeutic strategies for cancer treatment. This chapter focus on the key metabolic processes taking place in the normal and cancerous cellular conditions, while the latter has re-routed metabolic pathways to support its growth and proliferation. Further, this chapter describes the dominant influence of metabolic processes role in regulating oncogenic signaling pathways and transcription factors to target the metabolic activity of cancer.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Amino acid metabolism; Cancer metabolism; Fatty acid metabolism; Glucose metabolism; Pentose phosphate pathway; Warburg effect